1997
DOI: 10.1037/0012-1649.33.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Morphological spelling strategies: Developmental stages and processes.

Abstract: The spelling of many words in English and in other orthographies involves patterns determined by morphology (e.g., ed in past regular verbs). The authors report a longitudinal study that shows that when children first adopt such spelling patterns, they do so with little regard for their morphological basis. They generalize the patterns to grammatically inappropriate words (e.g., sofed for soft). Later these generalizations are confined to the right grammatical category (e.g., keped for kept) and finally to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
339
8
58

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(429 citation statements)
references
References 15 publications
24
339
8
58
Order By: Relevance
“…: Guimarães, 2005;Mota et al, 2008;Nagy et al, 2006;Nunes et al, 1997). No entanto, para a precisão e a fluência de leitura, pelo menos no que diz respeito ao português brasileiro, pode-se dizer que os resultados desse estudo questionam a contribuição da consciência morfológica.…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…: Guimarães, 2005;Mota et al, 2008;Nagy et al, 2006;Nunes et al, 1997). No entanto, para a precisão e a fluência de leitura, pelo menos no que diz respeito ao português brasileiro, pode-se dizer que os resultados desse estudo questionam a contribuição da consciência morfológica.…”
Section: Conclusãounclassified
“…Outra variável cognitiva da qual existem evidências de uma relação com a leitura e a escrita é a consciência morfológica (Carlisle, 1995;Guimarães, 2005;Mota, Anibal, & Lima, 2008;Nagy et al, 2006;Nunes, Bryant, & Bindman, 1997). De acordo com Carlisle, o termo consciência morfológica refere-se à ".…”
unclassified
“…spelt as they sound) and the conventional -ed was not yet used e.g., kist. This provided the evidence for the phonological stage Nunes et al (1997) anticipated that is prior to the development of morphological understanding.Stage three consisted of the use of some -ed endings but with overgeneralizations to irregular verbs and nonverbs, e.g., sleped, sofed. Nunes et al (1997) claimed these overgeneralization errors were of real significance and reported an unexpected finding.…”
mentioning
confidence: 94%
“…Early stage models (e.g. Frith, 1985) proposed that children gradually become more sophisticated in their spelling passing from an early "alphabetic stage" based on phonology and letter-sound correspondences to a later more sophisticated "orthographic stage" where higher order knowledge about spelling is acquired.Drawing upon this evidence and other more recent studies, Steffler (2001) concluded that a consensus has been reached within the literature, that spelling progresses from a visually based, phonological level, to a higher-order morphological level and then to a level where both of these aspects are taken into account, resulting in the correct production of spelling.Nunes, Bindman and Bryant (1997) provided support for this progression with a longitudinal study over three years using groups of children, aged 6, 7 and 8. At each of three sessions, participants did a spelling test of 30 words consisting of 10 regular past tense verbs, e.g.…”
mentioning
confidence: 99%
“…It demands integration of phonological, morphological, and orthographical information. Theories of spelling have proposed different interpretations of when and how the different components of knowledge are integrated in spelling (e.g., Nunes, Bryant, & Bindman, 1997;Pacton & Deacon, 2008;Templeton & Morris, 2000;Treiman & Cassar, 1996;1997;see Treiman & Kessler, 2014; for an overview). One viewpoint is that these skills are used and integrated gradually from an early age onwards (e.g.…”
mentioning
confidence: 99%